A Late Old Babylonian temple archive from Dūr-Abiešuḫ the sequel - Abraham, Kathleen 1963-; Van Lerberghe, Karel 1947-; Voet, Gabriela; Hameeuw, Hendrik (CDL Press, 2017)
Transliteration, photographs, and commentary on Babylonian cuneiform economic documents from the middle of the 2nd millennium BC.
Includes bibliographical references and index
Keywords: Cornell University -- Department of Near Eastern Studies -- Catalogs; Akkadian language -- Texts -- Catalogs; Keilschrifttext; Akkadisch; Babylonia -- Antiquities; Dūr-Abiešuḫ (Extinct city) -- History; Dūr-Abiešuḫ; Quelle